The "Phantom Costs" of Florida's Citrus Industry - Ronald P. Muraro; Fritz M. Roka; Thomas H. Spreen; Marcus Timpner (EDIS)
FE669, a 6-page fact sheet by Ronald P. Muraro, Fritz M. Roka, Thomas H. Spreen, and Marcus Timpner, describes a survey developed and implemented by a working group of growers and UF/IFAS personnel to determine the total costs of governmental regulatory compliance for citrus growers in Florida. Includes references and tables with example data and summaries of results. Published by the UF Department of Food and Resource Economics, January 2007.